Enhancing vocational high school students’ skills through 3D animation visual training in facing industry potential in the metaverse era - Sari, Intan Permata; Hendriyana, Hendriyana; Fajri, Bayu Ramadhani; Laksono, Alfan Pujo (Community Empowerment, 2025)
Vocational High Schools (SMK) are a part of formal education that aims to produce productive, work-ready graduates in accordance with 21st-century needs. However, the existing conditions are not in line with industry demands that require graduate competencies aligned with technological advancements. This community service program aims to enhance SMK students' skills in creating 3D animations, a technology that plays an important role in metaverse content creation. The program implementation method is an action research method consisting of introduction, training, and mentoring stages. Based on the evaluation results, the pre-test scores ranged from 24–54, and the post-test scores ranged from 46–94. This shows a 57.45% increase in skill abilities, with an average N-gain score of 0.66 (medium criteria), meaning that 3D visual training for facing industry in the metaverse era for SMK students is effectively used to improve abilities.